2021
DOI: 10.3389/fmicb.2021.663642
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Commodity Chemicals From Oil Palm Empty Fruit Bunch Lignin

Abstract: Lignin is one of the most abundant natural resources that can be exploited for the bioproduction of value-added commodity chemicals. Oil palm empty fruit bunches (OPEFBs), byproducts of palm oil production, are abundant lignocellulosic biomass but largely used for energy and regarded as waste. Pretreatment of OPEFB lignin can yield a mixture of aromatic compounds that can potentially serve as substrates to produce commercially important chemicals. However, separation of the mixture into desired individual subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Despite the success in enabling the production of the different non-natural molecules, in the specific case of levulinic acid, this platform has the problem of requiring a constant supply of succinate in the medium (since succinyl-CoA is used as a substrate in the first reaction), which, together with the low yield, can pose important constraints to the economic viability of the process. Another levulinic acid biosynthetic pathway was also recently assembled in E. coli using the degradation of ferulic and p-coumaric acids to produce 3-oxoadipic acid, which is then decarboxylated to yield levulinic acid (as detailed in Figure 5) [38]. Exploring metabolic retrobiosynthesis, a recent study from our group identified five promising levulinic acid production pathways from fermentable sugars (these are the pathways highlighted in grey in Figure 5) [65].…”
Section: Levulinic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the success in enabling the production of the different non-natural molecules, in the specific case of levulinic acid, this platform has the problem of requiring a constant supply of succinate in the medium (since succinyl-CoA is used as a substrate in the first reaction), which, together with the low yield, can pose important constraints to the economic viability of the process. Another levulinic acid biosynthetic pathway was also recently assembled in E. coli using the degradation of ferulic and p-coumaric acids to produce 3-oxoadipic acid, which is then decarboxylated to yield levulinic acid (as detailed in Figure 5) [38]. Exploring metabolic retrobiosynthesis, a recent study from our group identified five promising levulinic acid production pathways from fermentable sugars (these are the pathways highlighted in grey in Figure 5) [65].…”
Section: Levulinic Acidmentioning
confidence: 99%
“…Exploring metabolic retrobiosynthesis, a recent study from our group identified five promising levulinic acid production pathways from fermentable sugars (these are the pathways highlighted in grey in Figure 5) [65]. Interestingly, 3-oxoadipic acid was among the identified substrates for levulinic acid production in the computational search performed [38]. Other substrates identified included glutamate semi-aldehyde and δ-aminolevulinic acid, this later substrate being particularly interesting since the underlying pathway entails fewer heterologous steps than the others and is predicted to pose fewer constraints to the endogenous metabolism of yeast or E. coli cells [65].…”
Section: Levulinic Acidmentioning
confidence: 99%
“…S2), a pharmaceutical compound and central metabolite in the bketoadipate pathway. PCA can also be a platform compound for the production of diverse value-added chemicals, such as cis,cis-muconic acid, adipic acid and levulinic acid (31)(32)(33). However, conventional PCA production relies on extraction from plants with low yield and high cost (34).…”
Section: Introductionmentioning
confidence: 99%
“…Biological funneling for the conversion of lignin-related aromatic compound (LRC) mixtures to performance-advantaged bioproducts (13,14) has been demonstrated, and some of the associated bioproducts include 2-pyrone-4,6-dicarboxylic acid (15)(16)(17), itaconic acid (18), polyhydroxyalkanoates (8,19,20), cis,cis-muconic acid (21)(22)(23)(24), vanillin (25,26), substituted styrene molecules (27), pyridine-2,4-dicarboxylic acids (28,29), and β-ketoadipic acid (30), among others, reviewed recently by Weiland et al (12). β-Ketoadipic acid is a six-carbon dicarboxylic acid with a β-ketone (Fig.…”
Section: Introductionmentioning
confidence: 99%